METHODS OF MICROELECTRONIC OPERATION OF THE NPM-69-M BLOCK COMPLIANCE SCHEME - Ubaydullayev Saidazim Kahramonvich (Galaxy International Interdisciplinary Research Journal, 2021)
The article focuses on issues related to the use of electromagnetic relays and their localization, which is one of the major problems in railway transporti control systems. To solve these problems, the issues of modeling processes and the use of microelectronics devices, increasing efficiency and reliability have been considered. To solve these issues, the methods and methods of microelectronic devices were developed.